2021
DOI: 10.3389/fnins.2021.692575
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Based Falff: A Potential Novel Biomarker for Prediction of Radiation Encephalopathy in Patients With Nasopharyngeal Carcinoma

Abstract: Radiation encephalopathy (RE) is an important potential complication in patients with nasopharyngeal carcinoma (NPC) who undergo radiotherapy (RT) that can affect the quality of life. However, a functional imaging biomarker of pre-symptomatic RE has not yet been established. This study aimed to assess radiation-induced gray matter functional alterations and explore fractional amplitude of low-frequency fluctuation (fALFF) as an imaging biomarker for predicting or diagnosing RE in patients with NPC. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…Another application of the extracranial 125 I radiation method is to explore the extent, time course, and cellular feature of the recovery of HAN in mammalian brain, which may be also clinically relevant to radiation encephalopathy ( Kickingereder et al, 2014 ; Weusthof et al, 2021 ; Zhang et al, 2021 ). The SGZ contains a pool of neural stem cells that are quiescent or undergoing proliferation, with the latter event leading to both neuronal and glial genesis ( Del Bigio, 1999 ; Fares et al, 2019 ; Gage, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another application of the extracranial 125 I radiation method is to explore the extent, time course, and cellular feature of the recovery of HAN in mammalian brain, which may be also clinically relevant to radiation encephalopathy ( Kickingereder et al, 2014 ; Weusthof et al, 2021 ; Zhang et al, 2021 ). The SGZ contains a pool of neural stem cells that are quiescent or undergoing proliferation, with the latter event leading to both neuronal and glial genesis ( Del Bigio, 1999 ; Fares et al, 2019 ; Gage, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Imaging data were acquired on a Magnetom Tim Trio 3T scanner (Siemens, Munich, Germany) using blood oxygen level-dependent (BOLD) and three-dimensional T1-weighted magnetization prepared rapid acquisition gradient echo (MPRAGE) sequences. Scanning parameters for BOLD and three-dimensional (3D) T1 MPRAGE sequences are documented in our previous studies (Zhang et al, 2018(Zhang et al, , 2020a(Zhang et al, , 2021. Briefly, for the BOLD sequence, the parameters were as follows: repetition time (TR) = 2,400 ms, echo time (TE) = 30 ms, field of view (FOV) = 230 mm × 230 mm, matrix size = 64 × 64, time points = 240, flip angle = 90 • , and 40 axial slices.…”
Section: Magnetic Resonance Imaging Acquisitionmentioning
confidence: 96%
“…Recently, several studies have used non-invasive functional magnetic resonance imaging (fMRI) techniques to examine radiation-induced structural and functional alterations in gray matter (GM; Lin et al, 2017 ; Ding et al, 2018 ; Zhang et al, 2018 , 2021 ). Several studies of voxel-based morphometry (VBM) and surface-based morphometry have reported radiation-induced cortical volume, cortical thickness, and surface area abnormalities in multiple brain regions, such as the bilateral temporal lobes, the precentral gyrus, and the inferior parietal lobule (IPL; Lv et al, 2014 ; Lin et al, 2017 ; Zhang et al, 2021 ). Similarly, more recent fMRI studies have also documented altered regional neuronal activity and functional connectivity (FC) in the intratemporal and extratemporal lobes ( Ma et al, 2017 ; Qiu et al, 2018 ; Zhang et al , 2020a , 2021 ; Zhao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations